Recent and future development of the application of finite element analysis in clinching process - M. M, Eshtayeh; Hrairi, Meftah (Springer, 2016)
Clinching is a mechanical joining method using a simple toolset consisting of a punch, a die, and a blank holder. The shapes of these tools are the most important parameters that control the final geometry of the clinch joints and consequently the strength and quality of the latter. In order to save time and cost, these geometric parameters could be optimized by the use of finite element simulation. This paper reviews the published research related to the finite element modeling of the clinching process. In this study, a critical review of the latter had been carried out from different perspectives. The findings about difficulties facing the simulations of different clinching processes, the optimization of the process parameters, and the strength, joinability, and the quality of the joint were highlighted. In addition, future development, investigation, and more research are still needed to minimize problems and expenses in the industrial practical application of clinching.